Optimization of microwave-assisted extraction of phenolic compounds from Moringa oleifera Lam. processed dry leaves using response surface methodology - Sin, Kang (Animo Repository, 2010)
Moringa oleifera Lam. (MO), commonly known as drumstick tree, is one of Asian multipurpose tree. A few studies have reported the presence of phenolic compounds responsible for antioxidant activity in MO leaves. In this study, microwave-assisted extraction was employed to extract the phenolic compounds from the processed dry leaves powder of MO purchased from SECURA International Corporation (Makati city, Philippines). Fresh leaves collected from Las Pinas city, Philippines, were also used to determine the phenolic profile. To achieve high yield of total phenolic content (TPC), the extraction process parameters (extraction time, temperature, sample/solvent ratio, solvent composition, and microwave power) were optimized by using response surface methodology. The phenolic profile and antioxidant activities, based on ferric reducing/antioxidant power (FRAP) and 1,1-diphenyl-2-picryl-hydrazyl (DPPH) radical scavenging assays, of the extract obtained under the optimum conditions were also evaluated. The optimum conditions for the extraction of phenolic compounds were achieved at 5 minutes, 65 oC, 0.015 (g/ml), 35% by volume, and 360 W, for the extraction time, temperature, sample/solvent ratio, aqueous ethanol concentration, and microwave power, respectively. The predicted and the actual yield (16.7 mg /g dry leaf, and 16.5 mg/g dry leaf, respectively) of TPC at the optimum conditions were statistically equal, suggesting that the established model adequately predicted the response (TPC). In addition, the extract obtained at the optimum conditions exhibited high antioxidant activity (36.67 μmol Trolox equivalent/g dry leaf and 3.1 g dry extract/g DPPH, for FRAP and EC50 DPPH assay, respectively) compared to some plant extracts like Archangelica officinalis (13.8 μmol Trolox equivalent/g dry leaf), and Syzygium aromaticum (21.33 μmol Trolox equivalent/g dry leaf). Reverse phase high performance liquid chromatography analysis showed the presence of Gallic acid, Vanillic acid, p-Coumaric acid, Quercetin, and Kaempferol in the dry leaf extract obtained at optimum conditions. In the fresh leaf extract, on the other hand, only Quecertin was detected.